2017
DOI: 10.18203/2349-3933.ijam20170020
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C in the early diagnosis of diabetic nephropathy and its correlation with albuminuria

Abstract: Background: Diabetes mellitus (DM) refers to a group of common metabolic disorders that share the phenotype of hyperglycaemia. The metabolic dysregulations associated with DM causes secondary pathophysiological changes in multiple organ systems which result in various complications, responsible for the morbidity and mortality associated with the disease.Methods: The present study was undertaken in the Department of Medicine in collaboration with the Department of Biochemistry, of SGRDIMSR, Vallah, Sri Amritsar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Another study showed that the average serum cystatin C value was 1.73 in type 2 diabetic patients with normal urinary albumin levels, while the average serum cystatin C value was 2.07 in type 2 diabetic patients with microalbuminuria. These results suggest that serum cystatin C, as a renal glomerular filtration biomarker, is an earlier indicator of diabetic nephropathy than urinary microalbumin and serum Crn [35].…”
Section: Cystatin C (Cys-c)mentioning
confidence: 82%
“…Another study showed that the average serum cystatin C value was 1.73 in type 2 diabetic patients with normal urinary albumin levels, while the average serum cystatin C value was 2.07 in type 2 diabetic patients with microalbuminuria. These results suggest that serum cystatin C, as a renal glomerular filtration biomarker, is an earlier indicator of diabetic nephropathy than urinary microalbumin and serum Crn [35].…”
Section: Cystatin C (Cys-c)mentioning
confidence: 82%
“…The study suggested that serum cystatin C measurement is useful for the early detection of renal impairment in a way better than serum creatinine in the patients with diabetes. 16 Another study showed that the mean serum cystatin C values in type 2 diabetes with normoalbuminuria were 1.73 and in type 2 diabetes with microalbuminuria were 2.07 17 . The results show that the serum cystatin C values were raised in the patients with microalbuminuria.…”
Section: Resultsmentioning
confidence: 99%
“…1 Serum creatinine, estimated glomerular filtration rate (eGFR), blood urea, and urine albumin are typical indicators for the diagnosis and progression of diabetic nephropathy (DN). [2][3][4][5][6][7][8][9][10][11] Serum creatinine and eGFR are commonly used to evaluate renal function. However, it is noteworthy that a number of nonrenal variables, including age, weight, nutritional status, race, and gender, can affect serum creatinine levels.…”
Section: Introductionmentioning
confidence: 99%